Research on college stress and coping : implications from the COVID-19 pandemic and beyond - McCarthy, Christopher J.; Lynch, R. Jason; DiDonato, Stephen (Research on stress and coping in education series., 2024)
"This volume informs our understanding of how college settings can respond to the challenges of the COVID-19 pandemic and beyond. The college years are often a stressful time for students, but the pandemic has added unprecedented levels of demands. Much of what we know about stress and trauma in education predates the COVID-19 pandemic. As the pandemic recedes, it seems likely that promoting student health, always a challenge, will become even more difficult. Students faced steep losses in their academic and socio-emotional progress after more than two years of pandemic-impacted schooling. The silver lining is that scholars who study the occupational health have spent the past several years studying the effect of the pandemic on college students, which led us to edit this volume to collected what is known and have these experts explain how we can better support students in the future. Readers of this book will better understand the demands of the pandemic, as well as the resources college will need going forward"--